PEDAGOGICAL ACTION AND TECHNOLOGIES DURING ONLINE LEARNING: A CASE STUDY - Zakky Yavani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
Technology implementation has become a norm in today's teaching and Learning, including in EFL instruction at university level. However the investigation within pedagogy and technology fusion are rare to discuss. Therefore, this research investigates a lecturer's actions and technological performance in the learning process. This research uses descriptive qualitative, using case study principles. The data was taken from vocabulary class document, an interview three students of vocabulary for academic purposes class, and online class observation field notes. they aimed to determine the performance of pedagogy and technology in online Learning. The goal is to explain the pedagogical aspects of technology implementation seen from Laurillard’ persepectives (2012). It was found that pedagogical actions practiced are as follows; Narrative, interactive, adaptive, Productive, and Communicative pedagogical actions.